Reconstructing Independence of Indonesia’s Corruption Eradication Commission After Supervisory Board Reform in Criminal Justice - Putra, Agus; Pujianto, Nawan; Hutomo, Irfan Rizky; Esdarwati, Susila (al-Battar: Jurnal Pamungkas Hukum, 2025)
The Corruption Eradication Commission (Komisi Pemberantasan Korupsi/KPK) was established as an independent state institution under Law No. 30 of 2002 to address corruption as an extraordinary crime. However, its institutional independence experienced a significant shift following the enactment of Law No. 19 of 2019, particularly through the establishment of the Supervisory Board with authority to grant prior approval for pro justitia actions such as wiretapping, searches, and seizures. This article aims to analyze the implications of the Supervisory Board’s authority on the independence of the KPK and to formulate a normative reconstruction model that balances accountability and effectiveness within the Indonesian criminal justice system. Using normative legal research with statutory and conceptual approaches, this study examines national legislation, Constitutional Court Decision No. 70/PUU-XVII/2019, international standards under the 2003 United Nations Convention against Corruption (UNCAC), and comparative practices of anti-corruption agencies in Hong Kong and Singapore. The findings demonstrate that the ex-ante control model exercised by the Supervisory Board has the potential to undermine operational independence, efficiency, and confidentiality in corruption law enforcement. This article concludes that reconstructing KPK independence requires reformulating the Supervisory Board’s authority toward an ex-post oversight model, reaffirming the KPK’s independent constitutional position, and harmonizing oversight mechanisms with principles of good governance. Such reconstruction is essential to preserve public trust and ensure the effectiveness of corruption eradication in Indonesia.